The Influence of Transformational Leadership on Performance Employees With Affective Commitment as a Variable Mediation at the Binjai City Inspectorate Officethe Influence of Transformational Leadership on Performance Employees With Affective Commitment a - EDY PIMANTA TARIGAN; Kiki Farida Ferine (International Journal of Society and Law, 2024)
The purpose of this research is to determine and analyze the influence of Transformational Leadership on Employee Performance which is mediated by Affective Commitment in Binjai City Inspectorate Office Employees. This research was carried out at the Binjai City Inspectorate Office. The type of research is associative quantitative. The sample in this study was 60 employees of the Binjai City Inspectorate Office. The sampling technique in this research uses saturated samples so that the entire population will be a sample of 60 people. The research results show that Transformational Leadership has a significant influence on Employee Performance as shown by the T-Statistic value of 3.013 > 1.96 and the P Value of 0.003 < 0.05. On the influence of Transformational Leadership on Affective Commitment, the T-Statistic data obtained was 0.650 < 1.96 and the P-Value was 0.516 > 0.05 or there was no influence of Transformational Leadership on Affective Commitment. Affective Commitment has a significant effect on Employee Performance with a T-Statistic value of 6,322 > 1.96 with a P-Value of 0.000 < 0.05. In terms of indirect influence, the results show that Affective Commitment does not have a role as an intervening variable that will explain the relationship between Transformational Leadership and the Performance of Binjai City Inspectorate Office Employees. This shows that improvements in Transformational Leadership cannot increase Affective Commitment, which in turn cannot contribute to improving the performance of Binjai City Inspectorate Office Employees at the Binjai City Inspectorate Office.